MODEL PENGELOLAAN SUMBERDAYA MANUSIA BERBASIS KOMPETENSI ERA INDUSTRI 4.0: COMPETENCY-BASED HUMAN RESOURCE MANAGEMENT MODEL IN THE INDUSTRIAL ERA 4.0 - Nopi Hidayat; Musa Hubeis; Anggraini Sukmawati; Eriyatno Eriyatno (School of Business, Bogor Agricultural University (SB-IPB), 2020)
The symptoms caused by the existence of industry 4.0 indirectly encourage or force the organization to prioritize human resource management (Human Resource Management) so that it can last a long time and develop more advanced. This research was conducted to build a design model of competency-based human resource management across generations of the industrial era 4.0 using a soft system method. Generational differences that have been considered problems, are seen differently when the differences in the characteristics of the three generations (baby boomers, X and Y) are used as opportunities and complementary strengths in the challenges of the industrial world 4.0. In the current competency-based human resource management there are some gaps. The competency-based human resource management model across generations of 4.0 provides strategic steps taken in managing human resources. Keywords: generation, human resource management model, industry 4.0, soft sytem method